Die aanwending van tolke in maatskaplike werk - Devenish, Kenith (University of the Free State, 2002)
The conduction of social-work interviews, with specific reference to the assessment interview - during which communication by means of language comprises the primary building-block - forms an integral part of the process of providing assistance through social. work. Where language .and cultural differences exist between the social worker and the client/patient, this process may be disrupted. The lack of professional interpreters during social-work services hampers the interviewing process, since the social worker conducts interviews in a language that the client/patient does not understand.. The aim of this study is to describe the complexity of the use of an interpreter during multicultural social-work interviews; by focusing on the conduction of such interviews with the assistance of an interpreter. The particular focus of this study is an investigation into the current manner of putting all the generic phases of a social-work assessment interview into practice with the assistance of an interpreter: (These phases are: the pre-interview phase, the initial phase, the development phase, the closing phase and the post-interview phase.) The factors, variables and/or indicators that hamper the process of utilising an interpreter are also investigated, along with the indicators that should be included in a social-work guideline for the utilisation of an interpreter, as well as the additional competencies (knowledge, skill and attitude) which should be at the disposal of the social worker in order to ensure the result of effective utilisation of interpreters. In order to achieve the aim of this study, a literature study was undertaken, inter alia, which focused on the history and development of the social-work profession . and, in particular, multicultural social work. The role of the medical social worker as part of the multi-disciplinary team, as well as that of the hospital, the community and the client/patient, have also been investigated. The application of the socialwork principles, values and ethics within the generic phases of social-work interviews, has been explored and described throughout the study. However, interviews cannot be conducted without communication and, therefore, in-depth attention has been accorded to multicultural communication. The importance of cognitive and affective understanding and sensitivity during multicultural socialwork interviews has been amplified by means of indicators, in order to enhance multicultural understanding and sensitivity in social work. The utilisation of interpreters is laid down as a strategy in order to bridge multicultural problems, in cases where the social worker is not fluent in the client's/patient's language. The use of an interpreter is thus the means to multicultural communication, and is aimed at ensuring that the social-workassessment interview is understandable, as well as at facilitating comprehension during the whole course of the interviewing process. The interpreting process necessitates certain additional competencies on the part of the social worker and I the interpreter; but it should be borne in mind that the social worker manages and directs the interpreting process. The utilisation of an interpreter is an intricate and complex process which does not yet enjoy the necessary professional status and I recognition. The empirical investigation entailed the completion of questionnaires by all the medical social workers employed in the Free State. The client/patient group, the utilisation of interpreters, the interpreting process in general, as well as the generic phases of multicultural social-work interviews conducted with the aid of an interpreter, have been focused on. The generic phases of the social-work assessment interview conducted with the aid of an interpreter are not fully utilised by the medical social workers currently practising in the Free State. The process of utilising an interpreter is hampered by the presence and/or absence of factors, variables and/or indicators, such as, inter alia, the absence of professional interpreters, the absence of an ethical code and/or code of conduct for interpreters, as well as the absence of a guideline for the utilisation of interpreters in multicultural social work. Various indicators that should be included in a guideline for the utilisation of interpreters in social work are identified in this study. These generic phases, factors, variables and/or indicators are supplemented by the specialised competencies of the social worker during social-work interviews that areconducted with the aid of an interpreter. Valuable recommendations concerning social-work practice, theory, policy, research and training have been made on the basis of this study, such as, inter alia, the identification of indicators for inclusion in a guideline for the conduction of multicultural social-work interviews while using the services of an interpreter, which must be realised in practice.

Maatskaplikewerkonderhoudvoering met spesifieke verwysing na die assesseringsonderhoud, waartydens kommunikasie deur middel van taal die primêre bousteen is, vorm 'n integrale deel van die maatskaplikewerkhulpverleningsproses. Waar taal-·en kultuurverskille tussen die maatskaplike werker en die kliënt/pasiënt bestaan, mag hierdie proses versteur word. Waardevolle aanbevelings aangaande maatskaplikewerkpraktyk, -teorie, -beleid, -navorsing en -opleiding is.vanuit hierdie studie gemaak, soos onder andere die identifisering van indikatore vir insluiting in In riglyn vir multikulturele rnaatskaplikewerkonderhoudvoerinq tydens tolkbenutting . Maatskaplikewerkdienste sonder". professionele tolke belemmer die onderhoudproses aangesien die maatskaplike werker onderhoude voer in 'n taal wat die kliënt/pasiënt nie verstaan nie. Die doel van hierdie studie is om die kompleksiteit van tolkbenutting tydens multikulturele maatskaplikewerkonderhoudvoering te beskryf deur te fokus op multikulturele maatskaplikewerkonderhoudvoering met behulp van 'n tolk. Die studie is veral gerig deur 'n ondersoek na die huidige beoefening van al die generiese fases van 'n maatskaplikewerkassesseringsonderhoud met behulp van 'n tolk (te wete die voor-onderhoudfase, aanvangsfase, ontwikkelingsfase, afsluitingsfase en na-onderhoudfase). Ondersoek is ook ingestel na die faktore, veranderlikes en/of indikatore wat die tolkbenuttingsproses belemmer; die indikatore wat ingesluit behoort te word in 'n maatskaplikewerkriglyn vir tolkbenutting, asook die bykomende bekwaamhede (kennis, vaardigheid en houding) waaroor die maatskaplike werker moet beskik om effektiewe tolkbenutting tot gevolg te hê. Om die doel van hierdie studie te bereik, is 'n literatuurstudie onder meer onderneem wat gefokus het op die geskiedenis en ontwikkeling van die maatskaplikewerkprofessie en veral multikulturele maatskaplike werk. Die rol van die geneeskundige maatskaplike werker as deel van die multidissiplinêre span, die hospitaal, die gemeenskap en die kliënt/pasiënt, is ondersoek. Die toepassing van die maatskaplikewerkbeginsels, -waardes en -etiek binne die generiese fases van maatskaplikewerkonderhoudvoering is deurlopend verken en beskryf. Onderhoudvoering kan egter nie plaasvind sonder kommunikasie nie en daarom is indringend aan multikulturele kommunikasie aandag gegee. Die belangrikheid van kognitiewe en affektiewe begrip en sensitiwiteit tydens multikulturele maatskaplikewerkoriderhoudvoering is aangevul deur indikatore om multikulturele begrip en sensitiwiteit in maatskaplike werk te verbeter. Tolkbenutting word as strategie gestelom multikulturele probleme, waar die maatskaplike werker nie die kliënt/pasiënt se taal magtig is nie, te oorbrug. Tolkbenutting is dus die middel tot multikulturele kommunikasie en het die verstaanbare verloop van die maatskaplikewerkassesseringsonderhoud en die hele onderhoudproses ten doel. Die tolkproses noodsaak sekere bykomende bekwaamhede van die maatskaplike werker en die tolk, maar dit moet in gedagte gehou word dat die maatskaplike werker die tolkproses bestuur en rig. Tolkbenutting is 'n ingewikkelde en komplekse proses wat nog nie die nodige professionele status en erkenning geniet nie. Die empiriese ondersoek behels die invul van vraelyste deur al die geneeskundige maatskaplike werkers werksaam in die Vrystaat. Daar is op die kliënte-/pasiëntegroep, tolkbenutting, die tolkproses in die algemeen en die generiese fases van multikulturele. maatskaplikewerkonderhoudvoering met behulp van 'n tolk gefokus. Die generiese fases van die maatskaplikewerkassesseringsonderhoud met behulp van 'n tolk word nie volledig deur die huidige praktiserende geneeskundige maatskaplike werkers in die Vrystaat benut nie. Die tolkbenuttingsproses word deur die aan- en/of afwesigheid van faktore, veranderlikes en/of indikatore, soos onder meer die afwesigheid van professionele tolke, die afwesigheid van 'n etiese en/of gedragskode vir 'n tolk, asook die afwesigheid van 'n multikulturele maatskaplikewerktolkbenuttingsriglyn, belemmer. Verskeie indikatore wat ingesluit moet word in 'n riglyn vir tolkbenutting in maatskaplike werk word in die studie geïdentifiseer. Hierdie generiese fases, faktore, veranderlike en/of indikatore word aangevul deur die spesialis bekwaamhede van die maatskaplike werker tydens maatskaplikewerkonderhoudvoering met behulp van 'n tolk. Waardevolle aanbevelings aangaande maatskaplikewerkpraktyk, -teorie, -beleid, -navorsing en -opleiding is vanuit hierdie studie gemaak, soos onder andere die identifisering van indikatore vir insluiting in In riglyn vir multikulturele rnaatskaplikewerkonderhoudvoerinq tydens tolkbenutting.
Thesis (Ph.D. (Social Work))--University of the Free State, 2002
Keywords: Social service -- Translating; Interviewing; Counselor and client; Translating and interpreting -- Social aspects